Efficacy of green onion root extract in cosmetics and skin care products (Bioscience Journal, 2019)
In this study, leftover roots of Sansing green onions grown without toxic chemicals in Sansing Township, Ilan County, Taiwan were used as a raw material of skincare products. The raw material was extracted from the green onion roots by ultrasound in a low-temperature, safe and pollution-free environment. We hope to develop cleansers and other facial care products made of this natural, environmentally friendly, safe and affordable raw material so that people with sensitive skin can also use these products. We also hope that this study can contribute to circular economy and achieve the goal of green innovation by recycling the leftover roots. In terms of anti-oxidation, the DPPH free radical scavenging ability of 2.5 mg/mL green onion root extract was equivalent to 98% of that of 1 mg/mL BHT; the Fe2+ chelating ability was equivalent to 87.0% of that of 0.02 mg/mL EDTA; the superoxide anions scavenging ability of 2.5 mg/mL green onion root extract was equivalent to 84.2% of that of 1 mg/mL BHT and 80.4% of that of 0.05 mg/mL vitamin C. With respect to melanin synthesis inhibition, the green onion root extract's ability to inhibit dopachrome, the intermediate product of melanin, was positively correlated to its concentration, i.e., the higher the concentration of the green onion root extract, the better the inhibition ability. The IC50 of green onion root extract was 1.83 mg/mL, while, for comparison, the IC50 of vitamin C was 0.62 mg/mL. Furthermore, according to the cell survival assay, no obvious cytotoxic effect was found with the increase in the concentration of the green onion root extract. The whitening effect improved after 30 days of test. The improvement rate was 5.6% for 2.5 mg/mL green onion root extract, 3.1% for 1.25 mg/mL extract, and 1.7% for 0.625 mg/mL extract. The moisture retention also improved after 30 days of test. The moisture retention improvement rate was 22.7% for 2.5 mg/mL green onion root extract, 21.6% for 1.25 mg/mL extract, and 15.4% for 0.625 mg/mL extract. Based on the experiments, the green onion root extract obtained from ultrasound not only did not cause skin allergy and irritation but also showed anti-aging, melanin synthesis inhibition, whitening and moisture retention effects. The results showed that the green onion root extract can improve the moisture retention and whitening effect of the mask.